Promoting Renewable Energy in Longyearbyen: A Sustainable Means to Prevent Svalbard’s Environmental Degradation - Buonsanti, Fabio (Consilience, 2011)
This study aims to separately investigate: 1.The political reasons behind Norway‟s controversial decision to encourage a coal enterprise on Svalbard (an archipelago in the Arctic) and, 2.The current and future potential of wind and solar energy as untapped renewable sources, locally exploited through a hybrid wind-PV system. In doing so this preliminary study attempts to provide insights for the implementation of an alternative, sustainable strategy to keep a Norwegian year-round settlement at Longyearbyen, Svalbard, without any recourse to polluting mining operations. Such an eventuality, despite the need for further research, is promisingly described as feasible, environmentally advantageous and politically conceivable.